Performance Analysis of a Communal Residential Rainwater System for Potable Supply: A Case Study in Brisbane, Australia - Cook, Simon; Sharma, A.; Chong, M. (Springer, 2013)
Cities in developed countries have increasingly adopted rainwater tanks as an alternative water source over the last 15 years. The rapid uptake of rainwater tanks has been driven by the need to reduce demand for centralised water services that are under pressure to adapt to population growth and climate change impacts. Rainwater tanks are part of integrated urban water management approach that considers the whole water cycle to provide water services on a fit for purpose basis that minimises the impact on the local environment and receiving waters. Rainwater tanks are typically applied at the household scale for non-potable water source uses such as toilet flushing and garden irrigation. However, this paper reports on a communal approach to rainwater harvesting, where the water is treated for potable use. A communal approach to rainwater harvesting can offer benefits, such as: economies of scale for capital costs, reduced land footprint, centralised disinfection and flexibility in matching supply and demand for different households. The analysis showed that the communal approach could provide a reliable potable water source to a small urban development. However, there was an energy penalty associated with this water source compared to centralised systems that could be addressed through more appropriate pump sizing. The outputs from this monitoring and modelling study demonstrated rainwater harvesting can be expanded beyond the current mainstream practices of household systems for non-potable use in certain development contexts. The analysis contained in this paper can be used for the improved planning and design of communal approaches to rainwater harvesting. © 2013 Her Majesty the Queen in Right of Australia.